17β‐Oestradiol facilitates M2 macrophage skewing and ameliorates arrhythmias in ovariectomized female infarcted rats. Issue 12 (5th May 2022) - Lee, Cheng‐Che; Chen, Syue‐yi; Lee, Tsung‐Ming
Abstract: Epidemiological studies have suggested a lower incidence of arrhythmia‐induced sudden cardiac death in women than in men. 17β‐oestradiol (E2) has been reported to have a post‐myocardial infarction antiarrhythmic effect, although the mechanisms have yet to be elucidated. We investigated whether E2‐mediated antioxidation regulates macrophage polarization and affects cardiac sympathetic reinnervation in rats after MI. Ovariectomized Wistar rats were randomly assigned to placebo pellets, E2 treatment, or E2 treatment +3‐morpholinosydnonimine (a peroxynitrite generator) and followed for 4 weeks. The infarct sizes were similar among the infarcted groups. At Day 3 after infarction, post‐infarction was associated with increased superoxide levels, which were inhibited by administering E2. E2 significantly increased myocardial IL‐10 levels and the percentage of regulatory M2 macrophages compared with the ovariectomized infarcted alone group as assessed by immunohistochemical staining, Western blot and RT‐PCR. Nerve growth factor colocalized with both M1 and M2 macrophages at the magnitude significantly higher in M1 compared with M2. At Day 28 after infarction, E2 was associated with attenuated myocardial norepinephrine levels and sympathetic hyperinnervation. These effects of E2 were functionally translated in inhibiting fatal arrhythmias. The beneficial effect of E2 on macrophage polarization and sympathetic hyperinnervation was abolished by 3‐morpholinosydnonimine. Our results indicated that E2 polarized macrophages into the M2 phenotype by inhibiting the superoxide pathway, leading to attenuated nerve growth factor‐induced sympathetic hyperinnervation after myocardial infarction.